Consumer preference on lechon manok in Davao City a conjoint analysis - Carpina, Kharl Eves T. (2016)
Chicken was first domesticated for cockfighting. It is rich in protein and has relatively low amount of unsaturated fat which can help protect the heart against heart diseases. According to FAO, demand and consumption for chicken meat worldwide has been increasing. Roasted chicken, locally known as lechon manok, is prepared by roasting a whole chicken over a fire or a professional rotisserie. There is a lechon manok chain in almost every corner of the country which is a result of increase in consumption of poultry. The aim of this study is to understand the purchasing patterns of the lechon manok consumers in Davao City. This will be able to help the industry develop and keep up with the demand of its consumers. Those who have purchased lechon manok in Davao City are the key respondents of this study. A result showed that taste, size, and low price were among the top reasons why consumers purchase lechon manok. Majority of the respondents preferred to purchase from lechon manok near their place of residence. Also, the respondents were extremely concerned on the cleanliness of the retail outlet they are purchasing from. In addition, majority of the respondents purchase lechon 2-3 times a month. The results of the Conjoint Analysis showed that the size has the highest relative importance among the lechon manok attributes. The most preferred combination of lechon manok attributes is the one that is large, P150.00, African roast flavor, uling roasted and packaged with foil.